2017
DOI: 10.1161/atvbaha.116.307301
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Sex Chromosomes Cause Sex Differences in the Development of Cardiovascular Diseases

Abstract: This review summarizes recent evidence concerning hormonal and sex chromosome effects in obesity, atherosclerosis, aneurysms, ischemia/reperfusion injury, and hypertension. Cardiovascular diseases (CVD) occur and progress differently in the two sexes, because biological factors differing between the sexes have sex-specific protective and harmful effects. By comparing the two sexes directly, and breaking down sex into its component parts, one can discover sex-biasing protective mechanisms that might be targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
176
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(186 citation statements)
references
References 141 publications
3
176
0
Order By: Relevance
“…In this light, androgen signaling may play a broader role in aortic aneurysm and dissection, but the exact mechanism still needs to be elucidated. Prior experience in experimentally induced aneurysm in rodents has suggested that androgen signaling can exacerbate aortic wall inflammation, but little is known about the precise mechanism (51,(53)(54)(55)(56)(57)(58)(59). It is notable that in our mouse model of vEDS, the androgen-dependent risk seen at puberty was not associated with overt inflammation.…”
Section: Figure 6 Inhibition Of Oxytocin Signaling Decreases Erk Actmentioning
confidence: 80%
“…In this light, androgen signaling may play a broader role in aortic aneurysm and dissection, but the exact mechanism still needs to be elucidated. Prior experience in experimentally induced aneurysm in rodents has suggested that androgen signaling can exacerbate aortic wall inflammation, but little is known about the precise mechanism (51,(53)(54)(55)(56)(57)(58)(59). It is notable that in our mouse model of vEDS, the androgen-dependent risk seen at puberty was not associated with overt inflammation.…”
Section: Figure 6 Inhibition Of Oxytocin Signaling Decreases Erk Actmentioning
confidence: 80%
“…Risk factors for CAD differ between males and females due to differences in the genes carried by the X and Y chromosomes and in the sex hormones. [20,21]. Women display greater cardiac strength values than men, but male myocardia bers are more sensitive to calcium than are female bers [22].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of female menopause, and particularly of the hormone estrogen, is considered to be a main cause of such sex differences in plasma lipid parameter levels. Estrogen has been reported to have various protective actions on cardiac vessels [17,18]. It is generally accepted that this antiarter-iosclerotic action of endogenous estrogen can explain why the incidence of CAD is lower in premenopausal females than in males [19].…”
Section: Discussionmentioning
confidence: 99%